2019
DOI: 10.3389/fmats.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in NO2 Sensing Properties of Semiconductor-Type Gas Sensors by Loading of Au Into Porous In2O3 Powders

Abstract: Porous (pr-) In 2 O 3 powders loaded with and without noble metals (Au, Pd, or Pt) were prepared by ultrasonic spray pyrolysis employing the PMMA microspheres as a template (typical particle size (ps): 28 or 70 nm with a diameter), and their NO 2 sensing properties were examined. The Au loading on the pr-In 2 O 3 was effective to increase the NO 2 response at lower operating temperature (≤200 • C), while the metal loading of Pd or Pt were hardly effective. In addition, a decrease in the PMMA microspheres (from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In addition, our results suggested that Au loading promoted the adsorption of the negatively charged NO 2 species on the bottom part of the sensing layer, leading to an increase in the NO 2 response. The 0.5 wt% Au-loaded In 2 O 3 sensor showed the highest response to 0.25 ppm NO 2 at 30 • C among all the sensors in Table 1 [38]. However, their sensing properties to NO 2 are not yet confirmed under humidified atmosphere, especially at lower temperatures.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, our results suggested that Au loading promoted the adsorption of the negatively charged NO 2 species on the bottom part of the sensing layer, leading to an increase in the NO 2 response. The 0.5 wt% Au-loaded In 2 O 3 sensor showed the highest response to 0.25 ppm NO 2 at 30 • C among all the sensors in Table 1 [38]. However, their sensing properties to NO 2 are not yet confirmed under humidified atmosphere, especially at lower temperatures.…”
Section: Introductionmentioning
confidence: 91%
“…PMMA microspheres (ps: ca. 70 nm), which were synthesized by ultrasonic-assisted emulsion polymerization [38], were used as a polymer template. The aqueous dispersion containing the PMMA microspheres (37.5 cm 3 ) and In(NO 3 )•3H 2 O (1.77 g) was mixed with pure water (62.5 cm 3 ), and the mixture was served as an aqueous precursor solution.…”
Section: Preparation Of In 2 O 3 Powders By Ultrasonic Spray Pyrolysismentioning
confidence: 99%
See 3 more Smart Citations